Preeclampsia risk in oocyte donation versus double gamete donation pregnancies: a systematic review and meta-analysis - Joana Azevedo Gomes Augusto (2022)
The number of pregnancies achieved through gamete donation has escalated over the last decades. It has been hypothesized that double gamete donation pregnancies would have a higher risk of preeclampsia compared to single gamete donation pregnancies due to cumulative risk of preeclampsia in oocyte donation pregnancies and the separate risk associated with sperm donation. Therefore, a systematic review and meta-analysis was conducted to explore the association between double gamete donation pregnancies (DD) and the development of preeclampsia and gestational hypertension, comparing it with oocyte donation alone (OD). Five studies were included in the systematic review and four in the meta-analysis. No statistically significant differences were found in the risk of preeclampsia between study subgroups (odds ratio [OR] 0.82; 95% confidence interval [CI] 0.29-2.36). When considering only high-quality studies, a trend toward a higher risk of preeclampsia in DD was observed, although not statistically significant (OR 1.30; 95%CI 0.61-2.76; I2=0%, p 0.61). Regarding gestational hypertension risk, the pooled analysis did not find significant differences between OD or DD (OR 0.52; 95%CI 0.18-1.49; I2=84%, p 0.0003). In conclusion, women undergoing double gamete donation are not at higher risk of developing gestational hypertension or preeclampsia compared with those undertaking oocyte donation alone.